Chondroitin sulfate modified and adriamycin preloaded hybrid nanoparticles for tumor‐targeted chemotherapy of lung cancer. Issue 5 (19th December 2020) - Liang, Xiang; Liang, Xi
Abstract: Promising cancer treatment requires the assistant of drug delivery systems (DDS) with the aim to increase the accumulation of drugs in tumor tissue. Herein, a hybrid DDS was successfully developed to integrate chondroitin sulfate (CS) and calcium carbonate (CC) in to one system. Anticancer drug adriamycin (Adr) was preloaded into CC nanoparticles to obtain Adr‐loaded CC nanoparticles (CC/Adr). The resulted CS‐CC/Adr nanoparticles as a biocompatible DDS was able to specifically target cancer cells to enhance the chemotherapy of lung cancer due to the surface modification of CS. Intracellular uptake as well as in vivo imaging results revealed the obtained CS‐CC/Adr nanoparticles (size of 100 nm) showed CS mediated tumor specific accumulation into A549 and LLC cells than unmodified CC/Adr, in which the CD44 receptor might be involved, which finally resulted in stronger anticancer capability than Adr or CC/Adr. As a result, CS‐CC/Adr nanoparticles could be further extended to clinical administration in our future works.